Integrating complementary and alternative medicine into academic medical centers: Experience and perceptions of nine leading centers in North America - Vohra, Sunita (BioMed Central, 2005)
BACKGROUND: Patients across North America are using complementary and alternative medicine (CAM) with increasing frequency as part of their management of many different health conditions. The objective of this study was to develop a guide for academic health sciences centers that may wish to consider starting an integrative medicine program. METHODS: We queried North American leaders in the field of integrative medicine to identify initial sites. Key stakeholders at each of the initial sites visited were then asked to identify additional potential study sites (snowball sampling), until no new sites were identified. We conducted structured interviews to identify critical factors associated with success and failure in each of four domains: research, education, clinical care, and administration. During the interviews, field notes were recorded independently by at least two investigators. Team meetings were held after each visit to reach consensus on the information recorded and to ensure that it was as complete as possible. Content analysis techniques were used to identify key themes that emerged from the field notes. RESULTS: We identified ten leading North American integrative medical centers, and visited nine during 2002–2003. The centers visited suggested that the initiation of an integrative medicine program requires a significant initial outlay of funding and a motivated "champion". The centers had important information to share regarding credentialing, medico-legal issues and billing for clinical programs; identifying researchers and research projects for a successful research program; and strategies for implementing flexible educational initiatives and establishing a functional administrative structure. CONCLUSION: Important lessons can be learned from academic integrative programs already in existence. Such initiatives are timely and feasible in a variety of different ways and in a variety of settings.